Patient-reported hip pain and function are worse among elite Nordic ski athletes competing in ski jumping versus Nordic combined: a cross-sectional analysis - Vasavada, K. D.; Shankar, D. S.; Ross, K. A.; Avila, A.; Buzin, S.; Jazrawi, I. B.; Carter, C. W.; Chen, A. L.; Borowski, L. E.; Milton, H. A.; Gonzalez-Lomas, G. (Journal of ISAKOS, 2024)
Objectives Nordic ski athletes are at increased risk of developing hip pain and dysfunction secondary to femoroacetabular impingement syndrome (FAIS), but it is unclear whether hip symptomatology differs between ski jumping (SJ) and Nordic combined (NC) athletes. The purpose of this study was to compare patient-reported hip pain and dysfunction between elite Nordic ski athletes participating in SJ versus NC.